An Analysis of Arabic Language Learning Models in Takhassus Programs: Evidence from an Indonesian Pesantren - Muhammad Umar Zaid Alkhindi; Fiko Savero; Dimas Surya Nata; Anan Marliansyah; Hisbullah Huda; Mohamed Nasser (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to comprehensively examine the planning, implementation, and supporting and inhibiting factors of the Arabic Language Takhassus Program at As-Sakinah Islamic Boarding School in Sidoarjo. This research employs a qualitative, descriptive method, using observation, in-depth interviews with teachers and students, and analysis of curriculum documents. The findings reveal that the Takhassus Program is systematically designed through clearly defined objectives, tiered student grouping, and intensive evening learning schedules, with a strong emphasis on grammatical mastery and the study of classical Islamic texts (kitāb kuning). In its implementation, classroom instruction integrates traditional methods such as sorogan and bandongan with eclectic and communicative approaches. These are further reinforced through extracurricular language activities, including muḥāḍarah (public speaking), muḥādathah (conversation practice), and language olympiads. The program’s effectiveness is supported by strong institutional commitment, qualified instructors, and adequate facilities. However, several challenges persist, including inconsistent use of Arabic outside the classroom, heterogeneous student proficiency levels, the absence of standardized syllabi and lesson plans, and the suboptimal integration of educational technology. The study recommends strengthening curriculum design, standardizing instructional tools, and integrating educational technology to more comprehensively enhance the effectiveness and diversity of Takhassus-based Arabic learning models in Indonesia.